How did the red sun rise? : the origin and development of the Yan'an Rectification Movement, 1930-1945 - Gao, Hua, 1954-2011 (The Chinese University Press, 2018)
This work offers the most comprehensive account of the origin and consequences of the Yan'an Rectification Movement from 1942 to 1945. The author argues that this campaign emancipated the Chinese Communist Party from Soviet-influenced dogmatism and unified the Party, preparing it for the final victory against the Nationalist Party in 1949. More importantly, this monograph shows in great detail how Mao Zedong established his leadership through this party-wide political movement by means of aggressive intraparty purges, thought control, coercive cadre examinations, and total reorganizations of the Party's upper structure. The result of this movement not only set up the foundation for Mao's new China, but also deeply influenced the Chinese political structure today.